Clinical simulation at the training service. Perception of nursing technician apprentices - Zuleta Uribe, María Elena
The objective of this article is to analyze the perception of a group of technical education apprentices in nursing, in the exercise of cardiopulmonary simulation. This activity was carried out at the Centro de Gestión Tecnológica de Servicios ending the year 2021. With the theoretical support of Pamela Jeffries, David Ausubel and others, the clinical simulation was oriented towards meaningful and experiential learning contexts. The qualitative methodology used, was based on the triangulation of instruments that included a survey, interviews and participant observation, applied to volunteers with intentional sampling, interested in carrying out learning activities, using high and low fidelity equipment. There are many investigations worldwide related to the students' perception of simulated practices, but this work addresses a differential aspect that implies the improvement of comprehensive professional training, with a didactic strategy with an experiential focus. Two of the most significant results were: the use of technology is relevant because the relationship established between instructors and apprentices allows sharing and deepening learning. Secondly, the use of these active didactic techniques strengthens integral training, in dialogue with the institutional educational plan.